Qualities and supply of suitable dead wood for Ceruchus chrysomelinus and its dispersal pattern in a translocated population - Karlsson, Malin (SLU/Dept. of Ecology, 2012)
The wood-living beetle Ceruchus chrysomelinus is a rare species connected to natural forests. In Sweden, it is red-listed as endangered (EN) and an action plan for its preservation has been done by the Swedish Environmental Protection Agency. In this work I have therefore investigated how a translocation of the species succeeded after 17 years. I aimed to study the species dispersal biology, its substrate preferences and the supply of suitable wood on this site. The study was performed during 2012 in Pansaruddens nature reserve close to Uppsala in Sweden, which is a spruce dominated forest. In 1995 logs with dense populations of C. chrysomelinus were translocated into two locations within this reserve. Circular study plots were established with a radius of 75 m around the translocated logs in both sites. All lying dead wood trunks ≥10 cm in breast height within the study plots were investigated. Generalized linear models showed that the presence of C. chrysomelinus could be described by degree of decay, rot type (white/brown) and the size of the log. This study also shows that the species had dispersed within the two areas, but only for very short distances. Most findings were done <10 m from the translocated logs. On average the total amount of lying dead wood for the two study plots were 52 respectively 35 m3/hectare. Only 4 % of the total dead wood supply was suitable for C. chrysomelinus, when considering the wood qualities found important for the species in this study.